Design and Prototype Development of ATHERIA: A Smart Hospitality Intelligence System - Innocentius Dwijaya Lestari; Adhiwira Cavell Santoso (INSPIRE : Journal of Culinary, Hospitality, Digital & Creative Arts and Event, 2026)
The rapid advancement of artificial intelligence (AI) has accelerated digital transformation in the hospitality industry, yet many existing systems remain fragmented and lack integration. This study aims to design and develop ATHERIA (Artificial Hospitality Intelligence Assistant), a Smart Hospitality Intelligence System that integrates multiple hospitality service functions into a single AI-driven platform. The research employed a Design Science Research (DSR) approach consisting of problem identification, requirement analysis, system design, prototype development, and evaluation. A functional prototype was developed in a localhost environment, incorporating four core modules: Brain and Memory Core, Chat and Voice Request Interface, Search Catalog Engine, and Real-Time Dashboard Communication System. The prototype was evaluated through black-box testing and system integration assessment. The results demonstrated that all system functions operated according to predefined requirements, achieving a 100% functional success rate. This study contributes to the development of an integrated hospitality intelligence architecture that can serve as a foundation for future smart hospitality system implementation.